Effectiveness of Telehealth for Self-Care in Stroke Survivors: A Systematic Review - Sinaga, Dewi Sartika; Kariasa, I Made; Maria, Riri; Arista, Liya (STIKES Suaka Insan, 2025)
Declining self-care ability in stroke survivors impairs recovery and lowers long-termquality of life. This systematic review evaluates the effectiveness of telehealth interventionsin improving self-care capacity. Based on the PRISMA framework, five databases:PubMed, Science Direct, Scopus, Sage Journals, and ProQuest were searched for literaturepublished between 2020-2024. This search returned 387 results, of which 10 randomizedcontrolled trials were selected and evaluated according to a critical checklist. The resultsof this review suggest that self-care telehealth interventions significantly improve physical(mobility and muscle strength, performance of daily activities) and psychologicalcomponents (self-efficacy, depression and anxiety) that constitute a better quality of life.Telehealth technologies promote autonomy in stroke survivors by remote healthmonitoring, and lessen dependence on direct care. Yet, technological barriers and lowerdigital literacy in older and/or marginalized populations are challenges that must beovercome to achieve fair access and impact